Mapping China - !870290843!Wu, Chongqing ; ID: gnd/1116347520 (Brill, 2016)
Preliminary Material – Introduction /Chongqing Wu – 1 Small Farming in the Market Economy: A Study of a Village in Shandong, and Its Theoretical Significance /Yuan Gao – 2 “Beyond the Boundary”: A Countermovement to the Hollowing-out of Rural China /Chongqing Wu – 3 Social Ties and the Market: A Study of Digital Printing Industry from an Informal Economy Perspective /Tongxue Tan – 4 Discursive Dyslexia and the Articulation of Class: A Theoretical Perspective on China’s Young Female Migrant Workers (Dagongmei) /Ngai Pun – 5 The Class Formation: Control of Capital and Collective Resistance of Chinese Construction Workers /Ngai Pun , Huilin Lu and Huipeng Zhang – 6 Internet Mobilizing and Workers’ Collective Resistance at oem Factories /Jianhua Wang – 7 The Impacts of Labor Migration on Rural Poverty and Inequality /Shen Tan – Index. This collection includes seven articles from the journal Open Times, a window into contemporary Chinese academic trends. All the articles deal with the topic of “peasants, migrant workers and informal labor,” but each has a different emphasis. It illustrates various ways that people from a countryside make use of local social resources to seek out ways to making a living. In these models, we can still see traditional social networks, various degrees of ties based on kinship and locality, and the existence of humans as social groups. It also analyzes Dagongmei’s collective actions to fight against the capital and patriarchy, workers’ collective resistance at OEM factories, and the impacts of labor migration on rural poverty and inequality
10.1163/9789004326385
Keywords: Electronic books; !105605727!Aufsatzsammlung; ID: gnd/4143413-4; Peasants; Migrant labor; Informal sector (Economics); Rural population; Peasants; Economic conditions